Money Growth and Inflation: evidence from a Markov Switching Bayesian VAR - Gianni Amisano; Roberta Colavecchio (Hamburg University, Department Socioeconomics, 2013)
We contribute to the empirical debate on the role of money in monetary policy by analysing the features of the relationship between money growth and inflation in a Bayesian Markov Switching framework for a set of four countries, the US, the UK, the Euro area and Japan, over an estimation period spanning from 1960 to 2012. We find that the relationship between money growth and inflation appears to be nonlinear, as our estimation results identify multiple inflation regimes displaying clear and diversified features; moreover, as part of the model's information set, money growth plays a determinant role in the allocation of regimes. We show that observing monetary developments does (slightly) improve the signal of entering a high inflation regime but the influence of money on such signal seems to be relevant mainly in the 70s and the early 80s, i.e. in periods featuring exceptionally high rates of inflation. Our evidence confi?rms that the relationship between money and inflation appears to be relatively weak during periods featuring low and stable inflation.
Keywords: C11; C53; E31; 330; Money growth; infl?ation regimes; Markov Switching model; Bayesian inference